2016
DOI: 10.1111/pace.12889
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Different Catheter Ablations for Atrial Fibrillation: A Systematic Review and Meta‐Analysis

Abstract: The present systematic review and meta-analysis demonstrated that cryoballoon ablation was associated with greater freedom from AF, shorter procedural time, and lower rate of major complications, compared with radiofrequency ablation. Especially, CBA was more advantageous. However, MTCA seems promising for radiofrequency ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
0
7
1
Order By: Relevance
“…Cryotherapy was associated with shorter ablation time, but higher fluoroscopy time. Overall complication rate was 5.1% in our study, lower than the 13.5% rate reported in the Sustained Treatment of paroxysmal Atrial Fibrillation (STOP AF) trial [12]. However a large recently published metaanalysis shown that cryoballoon ablation seems to be associated with greater freedom from AF, shorter procedural time, and lower rate of major complications, compared with radiofrequency ablation [13].…”
Section: Resultscontrasting
confidence: 67%
“…Cryotherapy was associated with shorter ablation time, but higher fluoroscopy time. Overall complication rate was 5.1% in our study, lower than the 13.5% rate reported in the Sustained Treatment of paroxysmal Atrial Fibrillation (STOP AF) trial [12]. However a large recently published metaanalysis shown that cryoballoon ablation seems to be associated with greater freedom from AF, shorter procedural time, and lower rate of major complications, compared with radiofrequency ablation [13].…”
Section: Resultscontrasting
confidence: 67%
“…There have been two meta-analyses about pAF ablation published recently, but these studies differ significantly in the study inclusion criteria from our study. Xu et al (2016) published a meta-analysis this year that included retrospective, prospective, randomized and nonrandomized studies. Furthermore, all different ablation methods and all different stages of AF (pAF, persistent and permanent) were included.…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 99%
“…Recently, several RFC versus cryoballoon studies have been reported, and meta-analyses of these trials have demonstrated that RFC and cryoballoon share similar efficacy and safety profiles [ 7 10 ]. In fact, the FIRE AND ICE trial is the largest multicenter prospective randomized trial on catheter ablation, and this trial also demonstrated an equivalency between catheter groups with regard to safety and efficacy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a true comparison of RFC versus cryoballoon technology should be done in a large randomized population while using ILRs. Neither FIRE AND ICE nor the current meta-analyses use ILRs [ 5 10 ], and the true results of RFC efficacy could be overestimated while by comparison the cryoballoon results may be underestimated.…”
Section: Discussionmentioning
confidence: 99%